INJURIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
Injuries are a prevalent and often debilitating aspect of human life, affecting individuals across various age groups and demographics. This article delves into the intricate web of injuries, exploring their causes, consequences, and potential preventive measures. Through a systematic literature analysis, we aim to shed light on the diverse facets of injuries and their implications on physical and mental well-being. The methods employed in this study include an extensive review of existing research, statistical analyses, and a synthesis of findings. The results section unveils key patterns and trends, offering insights into injury prevention and management. The discussion section delves into the broader implications of the findings, and the conclusions and suggestions highlight avenues for future research and practical applications.